Economics of the Environment / Selected Readings - Dorfman Nancy S; Dorfman Robert (W.W. Norton & Company, 1972)
This volume provides a well-rounded set of tools for understanding and analyzing environmental problems, in the words of leading authorities. Preface, Introduction, An Overview, Analysis of Environmental Pollution, Federal Standards and Enforcement, Economic Analysis, Externalities and Information and Alternative Collective Action, The Problem of Social Cost, The Property Interface, Policies for Environmental Protection, Standards and Charges and Equity, Property Rights and Amenity Rights, A Public-Decision Model Applied to a Local Pollution Problem, The Convergence of Environmental Disruption, The Dynamics of Resource Use: Long-Run Considerations, The Environmental Costs of Economic Growth, The Structure of the World Models, Measuring Costs and Benefits, Criteria for Social Investment, Air Pollution and Human Health, Measure of Economic Welfare, Further Readings on Economics of the Environment.